Unveiling the future: A simulation and analysis of hydrogen production using 1kW electrolyzer with MATLAB approach - Yaw, Chong Tak; Paw, Johnny Koh Siaw; Kadirgama, Kumaran; Ramasamy, Devarajan; Ahmed, Oday A.; Pasupuleti, Jagadeesh; Benedict, Foo; Samylingam, Lingenthiran; Kok, Cheekuang (Elsevier B.V., 2024)
This research concentrates on optimizing hydrogen production via a 1kW electrolyzer powered by renewable solar energy, specifically targeting efficiency enhancement through adjusting membrane area. The rising global demand for clean energy solutions has positioned hydrogen as a pivotal element in the shift toward sustainable energy systems. Nonetheless, the efficacy of hydrogen generation via electrolysis continues to pose a challenge, particularly at reduced scales. This research involved the creation of a comprehensive simulation model utilizing MATLAB Simulink to investigate the impact of membrane area variations on hydrogen production and overall system efficiency. The simulation results indicate that optimizing the membrane area can substantially enhance hydrogen production rates. The system was capable of producing up to 2.5 kg/h of hydrogen, signifying a substantial enhancement over traditional methods. Moreover, incorporating solar energy as the principal power source diminishes environmental repercussions while guaranteeing a sustainable and clean approach to hydrogen production. This research introduces an innovative method for optimizing small-scale electrolyzers, offering insights applicable to industrial hydrogen production and the integration of renewable energy. The findings facilitate the advancement of sustainable hydrogen production technologies, consistent with international initiatives to diminish dependence on fossil fuels.